The Role of Nutritional Status on SARS-CoV-2 IgG Levels After COVID-19 Vaccination in Palembang - Ditta Puspa Anggraini; Eddy Mart Salim; Nur Riviati; Erial Bahar; Syamsu Indra; Nova Kurniati; Ahmad Rasyid; Yuniza (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The elderly and geriatric population is the population most at risk for complications of COVID-19. Preliminary data show that individuals aged >59 years are estimated to experience five times more severe COVID-19 symptom onset than those aged 30 to 59 years. Nutritional status is believed to play a role in the body's ability to produce antibodies after COVID-19 vaccination. Methods: A cross-sectional analytic observational study to determine the role of nutritional status on levels of IgG SARS-CoV-2 after COVID-19 Vaccination in Palembang. IgG levels were assessed by the ECLIA method. Data analysis was carried out univariate and bivariate. Results: The mean quantitative IgG of SARS-CoV-2 in underweight nutritional status was higher with a value of 5757.42±2594.08 U/mL and with the lowest mean quantitative IgG SARS-CoV-2 in overweight nutritional status with a value of 2998.13±4386.95 U/mL. Conclusion: Nutritional status did not play a role in SARS-CoV-2 IgG levels after the COVID-19 vaccination in Palembang.